2017
DOI: 10.3847/1538-4365/229/1/9
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Oscillations in Slender Ca ii H Fibrils Observed with Sunrise/SuFI

Abstract: We present observations of transverse oscillations in slender Ca IIH fibrils (SCFs) in the lower solar chromosphere. We use a 1 hr long time series of high-(spatial and temporal-) resolutionseeing-free observations in a 1.1 Å wide passband covering the line core of Ca IIH 3969 Å from the second flight of the SUNRISE balloon-borne solar observatory. The entire field of view, spanning the polarity inversion line of an active region close to the solar disk center, is covered with bright, thin, and very dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 95 publications
8
38
0
Order By: Relevance
“…This has given us the possibility to look at the structures present in the lower chromosphere at a level of detail not achieved before. Of special interest in this work are the so-called slender Ca II H fibrils (SCFs): similar to spicules or chromospheric jets, these ubiquitous features outline the magnetic field in the lower chromosphere and offer the possibility of gaining insight into the physical processes in this layer of the solar atmosphere (Pietarila et al 2009;Wöger et al 2009;Jafarzadeh et al 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…This has given us the possibility to look at the structures present in the lower chromosphere at a level of detail not achieved before. Of special interest in this work are the so-called slender Ca II H fibrils (SCFs): similar to spicules or chromospheric jets, these ubiquitous features outline the magnetic field in the lower chromosphere and offer the possibility of gaining insight into the physical processes in this layer of the solar atmosphere (Pietarila et al 2009;Wöger et al 2009;Jafarzadeh et al 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…The SCFs in this sequence were identified by restoring the Ca II H images in a multi-step procedure described in detail by Jafarzadeh et al (2017). In short, the inhomogeneities in the images due to non-uniform background solar intensity, noise, and geometric distortions are minimized using a real-space spatial bandpass filter (Jafarzadeh et al 2013) and the SCFs are modeled as bright elongated structures in the restored images.…”
Section: Sunrise Resultsmentioning
confidence: 99%
“…The physical properties of these SCFs have been investigated by Gafeira et al (2017b). In addition, Jafarzadeh et al (2017) and Gafeira et al (2017a) studied transverse and sausagemode oscillations in the SUNRISE/SuFI SCFs and provided propagation speeds of both types of waves.…”
Section: Introductionmentioning
confidence: 99%
“…However, Jess et al (2012) also found low-frequency intensity oscillations on the order of 2-9 mHz from their MHD simulations with grid size of 25km (i.e., spatial resolution of 50 km) and asimilar frequency resolution as in our study. Jafarzadeh et al (2017b) and Gafeira et al (2017) studied transverse oscillations and sausage-mode waves in bright, slender fibrils observed in a narrowband CaIIH passband (FWHM ≈ 0.11 nm) provided by SuFI during the second flight of the SUNRISE observatory . They found periods in the range of ≈20-160 s for both types of waves, with median values of roughly 83s and 34s for the transverse and sausage waves, respectively.…”
Section: Comparisons and Discussionmentioning
confidence: 99%